Ursodeoxycholic acid versus phenobarbital for cholestasis in the Neonatal Intensive Care Unit - Tamorah Lewis; Simisola Kuye; Ashley Sherman (BMC, 2018)
Abstract Background Although neonates and young infants with cholestasis are commonly treated with either phenobarbital or ursodeoxycholic acid (ursodiol), there is no evidence that phenobarbital is effective for this indication. Our objective was to compare the effectiveness of ursodiol and phenobarbital for the treatment of cholestasis in a diverse NICU population. Methods This is a retrospective cohort study including infants with cholestasis who were admitted to a Level IV NICU between January 2010 and December 2015. Drug courses of phenobarbital and ursodiol were identified within the medical record, and medical, demographic, and drug information were extracted. The primary outcome was reduction in direct bilirubin. Results Sixty-eight infants provided a total of 112 courses of drug therapy for comparison. Diverse medical diagnoses were captured in the patient cohort. Ursodiol was significantly more effective in reducing direct bilirubin than was phenobarbital (− 1.89 vs + 0.76 mg/dL; − 33.33 vs + 13.0 umol/L, p-value 0.03), even after controlling for baseline cholestasis severity, intrauterine growth restriction status, and lipid lowering therapy (− 2.16 vs + 0.27 mg/dl; − 36.94 vs + 4.62 umol/L, p-value 0.03). There was no improvement in direct bilirubin in the majority of infants treated with phenobarbital. Conclusions Phenobarbital, as compared to ursodiol, has limited efficacy for the reduction of direct bilirubin in neonates and young infants with cholestasis. Given new data regarding the potential neurotoxicity of phenobarbital in the developing brain, providers may choose to avoid phenobarbital in the treatment of cholestasis in infants.